STUDI KEBUTUHAN AIR DOMESTIK UNTUK DAERAH PANTAI (STUDI KASUS: KOTA BANDAR LAMPUNG) - Gatot Eko Susilo; Ofik Taufik Purwadi; Nurayni Nurayni (UNIVERSITAS LAMPUNG, 2014)
This study aims to investigate water domestic demand of people living in coastal area of Bandar Lampung City. The location of the study is in the Sukaraja area, Bumi Waras Sub-district, Bandar Lampung City. Data mining of household water demand is undertaken by using questionnaire to 65 households. It is indicated from the survey that every household averagely consits of 4 persons. Everry person spends about IDR 368 for 103.4 l of water domestic in daily basis. Daily water domestic demand of the people in the are study is quite different from the standard daily water domestic demand percapita. This deviation is due to the differences in the aspect of social and economy between the people in the are study and ordinary people